RICIKAN STRUKTURAL SALAH SATU INDIKATOR PADA PEMBENTUKAN GENDING DALAM KARAWITAN JAWA - Supardi Supardi (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2013)
Abstract Javanese gamelan set that has been existing since a long time ago untiltoday should be understood by the students of Karawitan Department of Performing Art Faculty of Surakarta Indonesian Art Institute (FSP ISI). Moreover, the acceptance of Learning Model Innovation and Development Proposal of Karawitan Practical Art Profession course in 2007 containing the Javanese gamelan set included the pakurmatan and gamelan ageng sets compulsorily attended by every student of Karawitan Department of ISI Surakarta. Those two gamelan sets should be attended for 7 semesters, in whichÂ there are a variety of norms or rules, including component grouping, gendingÂ form types, and etc. Martapengrawit, one of Javanese Karawitan Mpu, statesÂ that there are 16 gending forms: Lancaran, Ketawang, Ladrang, Merong, Inggah, etc. In addition, Rahayu Supanggah argues that structural composition (ketuk,kempyang,kenong, kempul, gong) is related to the gending form in Javanese karawitan. The writer also argues that component serves as one indicator of gending creation in Javanese karawitan.Key words: Javanese gamelan - exists - past - present-musical form - structural